Intestinal parasitic infections among artisans in Benin city, Nigeria - Akinbo, Frederick; Ikedje, Aghogho; Okaka, Christopher (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: Human intestinal parasites have always been a major health problem in the developing countries. This study was aimed at determining the prevalence of intestinal parasitic infections among artisans and establishes a relationship between the prevalence of intestinal parasitic infections and risk-factors. Materials and Methods: A total of 353 participants which consisted of 272 males and 81 females were recruited for this study with age ranging from 18 to 65 years. Stool specimens were collected from the participants and analysed using the standard technique. The data obtained were analysed using Chi-square (χ2) to compare the frequency data while the odd ratio was calculated for potential risk factors. Results: Out of 353 subjects, 118 (33.4%) subjects had intestinal parasitic infections. Age, gender, marital status, occupation, educational status and source of food did not significantly affect (P= 0.219,P= 0.920,P= 0.276,P= 0.087,P= 0.074 andP= 0.442, respectively) the prevalence of intestinal parasitic infections. The use of well/rain water (odds ratio [OR] =2.721; 95% confidence interval [CI] = 1.452, 5.100;P= 0.002) and presence of diarrhoea (OR = 6.169; 95% CI = 3.665, 10.474;P< 0.0001) were significantly associated with intestinal parasitic infections among artisans. Defecating in nearby bushes resulted in a significantly increased prevalence of intestinal parasitic infections among artisans (P< 0.0001). The intestinal parasites recovered were Ascarislumbricoides, hookworm, Trichuristrichiura and Entamoebahistolytica.A.lumbricoideshad the highest prevalence (77.8%). The male gender had the highest prevalence in all the four intestinal parasites recovered in this study. Conclusion: Overall prevalence of 34.4% of intestinal parasitic infections was observed among artisans in Benin City. The source of water, type of toilet and presence of diarrhoea significantly affected the prevalence of intestinal parasitic infections among artisans.A.lumbricoideswas the most prevalent parasitic agent recovered in this study.